Education for Financial Literacy on Children Educationonal Fund Among Housewives in West Jakarta - Ranteallo, Asrah Tandirerung; Herawati, Niken; Mulyani, Ade Sri (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study exactly aimed to analyze financial literacy and financial planning in children's education funds among housewives. Respondents in this study were 100 housewives who live in Jakarta city. The data of this research was obtained through the distribution of questionnaires and interviews to dig up more in-depth information. The collected data were analyzed using descriptive statistical analysis, namely to determine the level of financial literacy and financial planning in children's education funds. Based on the results of the analysis carried out, the following results were obtained: 1) The level of financial literacy in planning children's education funds among housewives in Jakarta is high; 2) Financial planning for children's education funds among housewives in the Jakarta city is also relatively high.